EFFECT OF SURYANAMSKARA AND YOGA PRACTICES ON SELECTED PHYSICAL AND PSYCHOLOGICAL VARIABLES AMONG GIRLS COLLEGIATE STUDENTS - S. Dessai, Gautami; Rajam, A. (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The objective of this study was to find out the effect of suryanamskara and yoga practices on selected physical and psychological variables among girls collegiate students. This research was based on pre-test and post-test group design. A total number of 45 girls students (15 - experimental suryanamskara & yoga practice group  and 15 - control group ) as samples aged 18-21 years were selected on the basis of purposively method of sampling technique from cuncolim educational society colleges of arts and commerce cuncolim, Goa state. The study was taken to the variables was physical and psychological variables. The selected subjects were pre-tested by 12 min run & walk Cooper test, sit & reach, sit-ups test and self concept Mukta Rani Rastogi questionnaire for psychology variable all test conducted before the programs implemented and after treatment of eight weeks suryanamaskar and yoga program on collegiate students which was given six days in a week was manipulated only on experimental group. After programs both the groups i.e, experimental were post tested for data collection. After data collection, data of pre-test and post-test of both the groups i.e, experimental and control group, compared by independent sample t-test and interpretation were drawn. The researcher made the conclusion that eight weeks suryanamskara and yoga program was significantly improvement of cardio vascular endurance, flexibility, muscular endurance and self concept of collegiate girls students of experimental group compared control group.